الاستثارة الحسية وعلاقتها بالذكاء العاطفي لدى طلبة معاهد اعداد المعلمين - م.د خنساء عبد الرزاق عبد (مجلة الفتح للبحوث التربوية والنفسية, 2023)
الملخص تعد الاستثارة الحسیة عاملا ً مھما ً في تطویر وتكامل شخصیة الإنسان وإذا كان إثراء عقل الإنسان ببیئة حسیة غنیة بالمثیرات تساھم في إتاحة الفرصة لطاقاتھ بالظھور فان العلاقة القویة بین الاستثارة الحسیة والذكاء العاطفي تدفع بالأفراد إلى المشاركة بشكل فعال في انجازاتھم واتخاذھم للقرارات الصائبة تجاه المواقف التي تواجھھم في حیاتھم الیومیة ، ومن ھنا تتجلى أھمیة الذكاء العاطفي للفرد إذ ان لدى الفرد انطباعا ً بأن مجموعة أفكاره منطقیة ومتسقة وان نظام أفكاره یحدد سلوك الفرد واتجاھاتھ ومعاییره وقیمھ وكل أفعالھ وأفكاره ومشاعره. وقد ھدف البحث إلى ما یأتي :- ١– قیاس الاستثارة الحسیة لدى طلبة معاھد إعداد المعلمین . ٢ -التعرف على الفروق في الاستثارة الحسیة على وفق متغیر النوع (ذكور– إناث). ٣ -قیاس الذكاء العاطفي لطلبة معاھد إعداد المعلمین. ٤-التعرف على الفروق في الذكاء العاطفي على وفق متغیر النوع( ذكور – إناث ). ٥ -إیجاد العلاقة بین الاستثارة الحسیة والذكاء العاطفي لدى طلبة معاھد إعداد المعلمین. وتحقیقا ً لأھداف ھذا البحث تم تطبیق أداتي قیاس الاستثارة الحسیة والذكاء العاطفي وقد قامت الباحثة بتكییف مقیاس الاستثارة الحسیة على طلبة معاھد إعداد المعلمین ،وقد تألفت عینة البحث من ( ٣٠٠ ( طالب وطالبة في معاھد إعداد المعلمین تم اختیارھم بطریقة عمدیة من معاھد إعداد المعلمین في بعقوبة. وبعد تحلیل البیانات ومعالجتھا إحصائیا ً باستعمال الاختبار التائي لعینة واحدة والاختبار التائي لعینتین مستقلتین توصلت الباحثة إلى النتائج الآتیة :- ١ -یتصف طلبة معاھد إعداد المعلمین بالاستثارة الحسیة . ٢ -لا توجد فروق ذات دلالة إحصائیة معنویة في الاستثارة الحسیة تبعا ً لمتغیر النوع . ٣ -یتصف طلبة معاھد إعداد المعلمین بمستوى جید من الذكاء العاطفي. ٤ -تفوق الذكور على الإناث في الذكاء العاطفي. ٥ -وجود علاقة ارتباطیھ موجبة بین الاستثارة الحسیة والذكاء العاطفي لدى طلبة معاھد إعداد المعلمین. وفي ضوء نتائج البحث توصلت الباحثة إلى العدید من التوصیات و المقترحات منھا:- أجراء دراسة تتناول الاستثارة الحسیة وعلاقتھ ومتغیرات نفسیة أخرى مثل ( تقدیر الذات والفعالیة الذاتیة و الإبداع). Sensation Seeking and Its relation WithEmotional intelligence for Students of teacher training institutes By Dr. Khansa Abdul Razaq Abd Directorate of Education Diyala / Institute of preparation parameters Abstract Actually sensation seeking is considered to be an important factor in developing and achieving of self consistency. In case of enhancing for the individual mind to be effected by rich sensitive environment which in turn take part in allowing the human abilities and powers to be discovered , this means that a strong relationship between sensation seeking and Emotional intelligence pushes the individuals to participate actively in achieving and right decision making towards a daily life –faced situations We can conclude the importance of Emotional intelligence f by the individual him/her self , just for having an impression that a group of their ideas are to be consistent and reasonable .in addition that his –her system of ideas play a great role in determining the individuals’ behaviors ,directions , criteria and their values . Their actions, ideas, and feelings are to be consistent with their system of mind ideas . This research aims to the following: 1-Measuring the sensation seeking of Students of teacher training institutes. 2- Signify the conditions of sensation seeking the according to of type (males –females) . 3- Measuring the Emotional intelligence of Students of teacher training institutes. 4- Signify the conditions of Emotional intelligence the according to type (males –females) . 5- Finding a relationship between the Emotional intelligence and sensation seeking for the Students of teacher training institutes. For fulfilling the goals of this research. so the researcher implicated the doubled tools of measuring the sensation seeking and Emotional intelligence on the samples of 300 Students of teacher training institutes. that hve been selected Sample deliberate from Baquba sity. After analyzing and processing the date statistically by using T tests on one sample and T tests on two independent samples .All those tests concluded the research with the following results :- 1-The Students of teacher training institutes are featured with sensation seeking . 2-There is no semantic statistic meaningful difference in the sensation seeking on the basis of the type variable. 3 – The Students of teacher training institutes are featured with Emotional intelligence. 4- The males are more Emotional intelligence than the females. 5 –There is a positive associated relationship between the Emotional intelligence and sensation seeking of the Students of teacher training institutes . In the light of those results , the researcher has some recommendations:- It is important to get study about the sensation seeking and its relationship with other variables such as the self evaluation, the self-activity and the effectiveness .